Fertilization strategies alter growth and rhizosphere microbiome diversity in white potato (Solanum tuberosum) - ALUH NIKMATULLAH; MUHAMMAD SARJAN; AMRUL JIHADI; IHLANA NAIRFANA; EKA SUNARWIDHI PRASEDYA (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Nikmatullah A, Sarjan M, Jihadi A, Nairfana I, Prasedya ES. 2026. Fertilization strategies alter growth and rhizosphere microbiome diversity in white potato (Solanum tuberosum). Biodiversitas 27 (1): d270135. https://doi.org/10.13057/biodiv/d270135. Excessive inorganic fertilization is widely used to boost potato productivity, but often reduces nutrient-use efficiency and disrupts soil microbial communities. This study evaluated how three fertilization regimes viz. CF100 (100% recommended inorganic + organic fertilizer), CF50 (50% recommended inorganic + organic fertilizer), and CF50OF (50% recommended inorganic + organic fertilizer + biofertilizer), affect plant growth, yield, and rhizosphere microbiome composition of white potato (Solanum tuberosum). Growth assessments at five weeks after shoot emergence showed that CF50OF produced significantly higher shoot numbers, fresh biomass, and dry biomass compared to CF50, and achieved growth comparable to CF100. Tuber yield did not differ significantly among treatments. Amplicon sequencing of rhizosphere soil revealed that fertilization strategy strongly shaped microbial richness, taxonomic composition, and phylogenetic structure. CF100 exhibited the highest observed taxa and phylogenetic diversity, whereas CF50OF enriched a broader spectrum of low-abundance and functionally diverse microbial genera associated with nutrient cycling, organic matter degradation, hormone production, biocontrol, abiotic stress adapters, and other functions. Despite lower Shannon and Simpson diversity values compared to CF100 and CF50, CF50OF supported microbial communities with greater functional potential, which may compensate for reduced inorganic inputs. These findings demonstrate that integrating biofertilizer with reduced inorganic fertilizer can sustain potato growth while promoting a more ecologically functional rhizosphere microbiome, offering a promising strategy for nutrient-efficient and environmentally sustainable potato cultivation.